African biblical hermeneutics on the threshold? Appraisal and wayforward - Speckman, M. (Acta Theologica, 2016)
What appears to be African Biblical Hermeneutics often refers to the geographical location of the authors rather than the content. There always appears to be something new on the horizon, but the colonial umbilical cord prevents a crossing of the threshold. This article contends that, in order for it to cross the threshold, African Biblical Hermeneutics has to go beyond the geographical location of the reader/interpreter to the development of a framework that is essentially African, while not compromising the catholicity of the church. A celebration of life is proposed as the closest interpretative framework to both the Bible and the multiple African cultures.